Rediscovering Anatolia: Fire of Anatolia - Çağlı Kaynak, Elif; Ceyhan, Ahmet İlkay (Diamond Scientific Publishing, 2024)
In dance, which can be considered a form of representation, it is crucial to examine how elements are addressed and presented to the audience through a particular narrative. This process is not independent of political, cultural, and historical contexts. The dance troupe Fire of Anatolia, which emerged in the early 2000s under the name “Sultans of the Dance” and continues to exist today as Fire of Anatolia, presents its performances with an approach centered around multiculturalism and pluralism. The elements shaped around the Anatolian theme in their dance show parallels with the discourses of the Anatolianism movement in the historical context of thought, and the narrative presented through dance can also be interpreted as a reinvention of a tradition. Given Fire of Anatolia’s activities both domestically and internationally over the past 25 years, it is possible to discuss how these activities influence the perception of Türkiye within the framework of public diplomacy and national brand creation. In light of this, the aim of this study is to identify which traditions Fire of Anatolia has reconstructed from which perspectives, and to evaluate the international country image it has created. This analysis is based on visuals found on the dance group’s official page and statements made by the general art director during various programs.
Keywords: Fire of Anatolia; Cultural Diplomacy; Nation-Branding; Cultural Communication; Political Communication; Anatolianism